Lapse-Based Insurance - Gottlieb, Daniel; Smetters, Kent (American Economic Review, 2021)
Most individual life insurance policies lapse, with lapsers cross-subsidizing non-lapsers. We show that policies and lapse patterns predicted by standard rational expectations models are the opposite of those observed empirically. We propose two behavioral models consistent with the evidence: (i) consumers forget to pay premiums and (ii) consumers understate future liquidity needs. We conduct two surveys with a large insurer. New buyers believe that their own lapse probabilities are small compared to the insurer’s actual experience. For recent lapsers, forgetfulness accounts for 37.8 percent of lapses while unexpected liquidity accounts for 15.4 percent. (JEL D91, G22, G52)